Evaluation of commercial dipping oil for production of quality raisins from Thompson Seedless grapes - Ajay Kumar Sharma (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2017)
Grape growing in India is mainly confined to tropical peninsular regions of Maharashtra, Karnataka and Tamil Nadu. It is estimated that approximately 95% of total grapes are produced in Maharashtra and Karnataka alone. About 71 per cent of total grape production of the country is consumed as fresh and 27 per cent is processed into raisins. Grape drying is mainly concentrated in Sangli, Solapur and Nashik districts of Maharashtra and Vijayapura and Bagalkot districts of Karnataka. Generally, after dipping of grape bunches in solution of ethyl oleate and potassium carbonate (also known as Australian dip) the grape bunches are spread on nylon mesh inside grape drying shed and within 10-15 days drying process completed. There are several commercial products/substitutes for dip treatment available in the market. However, it has been reported that effectiveness of these products is variable. Therefore, present investigation was carried out to study effectiveness of a new commercial product for raisin production from Thompson Seedless grape variety in comparison to ethyl oleate. Grape bunches of Thompson Seedless were dipped in these solutions prior to drying inside raisin drying shed. Besides, the drying bunches were also sprayed with different concentrations of these products on 3rd and 5th days of drying. Observations were recorded on drying dynamics, browning index, colour intensity, content of phenols and tannins, sensory properties and quality parameters after storage for 4 months. It was observed that the dip treatment of Thompson Seedless grapes with a solution of 18 ml commercial product and 24 g potassium carbonate per litre of water for 2 minutes and sprays of 12 ml commercial product +16 g potassium carbonate per liter water on 3rd day and 6 ml commercial product + 8 g potassium carbonate per liter water on 5th day was found better than ethyl oleate for production of good quality raisins.